A comparison of relative humidity calibration facilities at temperatures up to 170 °C. (15th February 2022) - Peruzzi, A.; Bosma, R.; Tabandeh, S.; Fernicola, V.; Georgin, E.
Highlights: SI-traceability of relative humidity extended to very high dew-point temperatures. Degree of equivalence of three national humidity measurement standards. Demonstrated relative humidity calibrations at very high dew-point temperatures. Abstract: Three European National Metrology Institutes (NMIs), VSL, LNE-CETIAT and INRiM, extended their relative humidity calibration capabilities to temperatures up to 170 °C, dew-point temperatures up to 150 °C and pressures up to 600 kPa. In order to test the equivalence of the respective calibration set-ups, 4 commercial high-temperature relative humidity sensors were exchanged among the three NMIs and calibrated at different combinations of relative humidity (19 %rh to 70 %rh), air temperature (100 °C to 170 °C) and pressure (100 kPa to 500 kPa), realizing dew-point temperatures of either 81.5 °C or 127 °C. The initial and final measurements at VSL showed that the stability of the selected sensors was sufficient for comparing the different calibration set-ups. The results of the comparison showed that VSL and LNE-CETIAT facilities agreed within their claimed uncertainties (≤0.3 %rh), while discrepancies of up to 4 %rh were observed between VSL and INRiM facilities.